Learning Outcomes Through Workshop Participants Motivation Based from the Economic and Educational Background - Windra Irdianto (Pascasarjana Universitas Negeri Malang (UM), 2014)
Hasil Belajar Melalui Motivasi Peserta Diklat Ditinjau dari Latar Belakang Ekonomi dan PendidikanAbstract: The purpose of this study to describe (1) direct influence of economy level towards motivation, (2) direct influence of education level towards motivation, (3) direct influence of economic level towards learning achievement, (4) direct influence of education level towards learning achievement, (5) direct influence of motivation towards learning achievement. The data is collected by using questionnaires and documentation analysis of 160 training participants, and path analysis is the technique that is used by the researcher. The findings show that, (1) there is a direct influence of economy background of members parents towards the training members motivation in following training, (2) there is a direct influence of education background of the training members towards the training members motivation in following training, (3) there is not a direct influence of economy background of members parents towards the training members learning achievement in following training, (4) there is a direct influence of education background of the training members towards the training members learning achievement in following training, (5) there is a direct influence of motivation towards training member’s learning achievement in following training.Key Words: learning achievement, motivation, economy background, education backgroundAbstrak: Tujuan penelitian ini untuk menjelaskan (1) pengaruh langsung tingkat ekonomi terhadap motivasi, (2) pengaruh langsung tingkat pendidikan terhadap motivasi, (3) pengaruh langsung tingkat ekonomi terhadap hasil belajar, (4) pengaruh langsung tingkat pendidikan terhadap hasil belajar, (5) pengaruh langsung motivasi terhadap hasil belajar. Data dikumpulkan dengan menggunakan metode angket dan analisis dokumentasi dari 160 peserta diklat, dan teknik analisis data dilakukan dengan analisis jalur (path analysis). Hasil penelitian adalah: (1) terdapat pengaruh langsung latar belakang ekonomi orang tua peserta diklat terhadap motivasi belajar peserta diklat dalam mengikuti kegiatan diklat, (2) terdapat pengaruh langsung latar belakang pendidikan peserta diklat terhadap motivasi belajar peserta diklat dalam mengikuti kegiatan diklat, (3) tidak terdapat pengaruh langsung latar belakang ekonomi orang tua peserta diklat terhadap hasil belajar peserta diklat dalam mengikuti diklat, (4) terdapat pengaruh langsung latar belakang pendidikan peserta diklat terhadap hasil belajar peserta diklat dalam mengikuti kegiatan diklat, (5) terdapat pengaruh langsung motivasi belajar peserta diklat dalam mengikuti kegiatan diklat terhadap hasil belajar peserta diklat.Kata kunci: hasil belajar, motivasi, latar belakang ekonomi, latar belakang pendidikan